Victor Grant Collection, Album 4, Photograph 140 4th of July gathering at Abreu home, Rayado, New Mexico
Left to right: Individuals 1, 2, 3 unknown. 4. Josefita Abreu Clouthier. 5. Petra Beaubien Abreu. 6. Adlina Abreu Valdez. 7. Emilio Valdez. 8. D. A. Clouthier. Individual 9 unknown. 10. Viola Clouthier Webster. Individuals 11, 12, 13, 14 and 15 unknown. 16. Ramon Abreu. 17. Gertrude Brown Abreu. Individuals 18, 19 and 20 unknown.
Designation "4.140" in listing stands for Album 4, Photograph 140.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Abreu Family; Maxwell - Beaubien family; Genealogy - Photographic collection. -- New Mexico